The Effect of Extensive Reading on the Vocabulary Mastery at the Seventh Grade Students of Junior High School - Halimatus Sa'diyah (JournEEL, 2021)
The objective of this research was to know there was influence effect between extensive reading on the vocabulary mastery at the seventh-grade students of junior high school of MTs Hasyim Asy’ari Sukodono. The subject of this research is 7.1 and 7.2 students from the seventh grade. The method used in this research quasi-experimental. In collecting the data, the researcher used four steps that was analyzed. The first step was pre-test to the both experimental and control group. The second step was giving treatment in terms of extensive reading process to the experiment group. The next step was giving post-test to the both control and experimental group. Then, the fourth step was to know whether the opinion of the students about extensive reading for the vocabulary mastery using questionnaire. In analyzing the data, the researcher analyzed them by using statistical analysis in SPSS 16.0 by comparing the result of pre-test and post-test from the students. The result of data from this research was counted to know whether the experiment was successes or not. The result of this research shows that there is an effect between extensive reading on the vocabulary mastery. Based on the study presented that sig. 2 tailed (p) was 0.003 though alpha (α) was 0.05. It means p < α. It can be concluded that the HO (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. It proved that extensive reading is effective in improving students’ vocabulary mastery.